Analisis Profitabilitas Pada PT. Fast Food Indonesia tbk - Ayub Usman Rasid (Gorontalo Management Research, 2018)
Profitability Analysis At PT. Gelael Praktis Makassar. This study aims to see the company's ability to generate profits by analyzing financial data for the last five years.           The expected result, the method of analysis used in this research is to use cross margin ratio analysis, profit margin ratio, return on asets and return on equity. The results of this study indicate that the profitability ratio owned by the company over the last five years fluctuated but still in good condition.